Technology for creating digital cartographic data and tools for digitizing maps with a solid base - Adilkhan Айман (Рroblems of engineering and professional education, 2023)
The article considers the main stages of creating a digital cartographic map. In this work, great attention is paid to the importance of mapping and updating all scale series of maps. This approach will certainly be interesting for specialists in the field of cartography.